EXAMINING THE IMPACT OF DUAL ROLE CONFLICT, JOB STRESS, AND TRANSFORMATIONAL LEADERSHIP ON TEACHER JOB SATISFACTION - Simanungkalit, Syahriati; Septiano, Renil; Sari, Laynita; Marwan, Marwan; Firmansyah, Indra (Yayasan Education and Social Center, 2025)
This study aims to analyze the influence of dual role conflict, work stressors, and the principal’s transformational leadership on teacher job satisfaction at SMP Negeri 1 Pagai Utara Selatan. A quantitative approach was employed with a total of 33 teacher respondents selected through total sampling, meaning the entire population was included as the sample. The research instruments were developed based on indicators of each variable, and the collected data were analyzed using multiple linear regression techniques. The results show that dual role conflict and work stressors have a negative impact on teacher job satisfaction, while transformational leadership from the school principal has a positive effect. Both partially and simultaneously, these three variables significantly influence teacher job satisfaction. These findings emphasize that in order to improve job satisfaction, it is essential to implement management strategies that minimize role conflict and work-related stress, while also promoting a leadership style that is inspirational, supportive, and capable of encouraging teachers’ professional development within the school environment.